PENINGKATAN KEMAMPUAN MOTORIK HALUS PADA ANAK USIA PRASEKOLAH DENGAN KEGIATAN LOMBA MEWARNAI DI DESA KRANGGANHARJO KECAMATAN TOROH - Sutiyono; Alfira Triska Maharani; Risma Aisya; Defyan Ahmad Muflizar; Aripin; Satriya Hendi Rega Dani; Ani Wahyuni; Latifatu Siyadah; Nieken Luh putu; Rahmania Isabel; Putri Syifa Ratu Ayu Jelita; Yuliyant; Shinta Amalia; Hanny Novita Sari; Erni Pustikha Sari; Meila Cindy Putri Lestari; Nur Intan Permatasari; Nurlia Fitrianingrum; Irsa Riswanda; Fiana Khayu Maftuhah; Siti Avitasari (LPPM AN Nuur, 2023)
Background: The environment and family play an important role in children's growth and development. There are still many preschool age children who still lack fine motor development due to a lack of stimulation and parental care because parents are indifferent to the development of children's fine motor skills. Methodology: This activity was carried out to find solutions to problem solving through village community deliberations and then implemented through a coloring competition activity. Results: After the coloring competition activity, fine motoric development in preschool children increased and parents understood fine motoric development in children Conclusion: Parents' knowledge about fine motor development increases, children can carry out tasks well, children's willingness to color contributes to fine motor development in preschool children.